STUDI PERSEPSI – SIKAP NELAYAN LOKAL DAN ANDON TERHADAP HAK PEMANFAATAN SUMBERDAYA PERIKANAN DI KAMPUNG BALIKUKUP KECAMATAN BATU PUTIH KABUPATEN BERAU, PROVINSI KALIMANTAN TIMUR - Muhammad Zaini Nur Hafid; Bambang Indratno Gunawan; Erwiantono (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purpose of this study was to know perceptions - attitudes of local fishermen and andons towards fishery resources utilization rights in Balikukup Village. The sampling method used was purposive sampling with 20 respondents consisting from local fishermen and andons with professions as ship masters and crew. The results of this study indicate the perceptions of local fishermen in Balikukup village, both those who refused and those who received the knowledge of government regulations or regulations to regulate fisheries resource utilization rights, by Andon fishermen outside their domicile. The attitude of local fishermen who disagreed with the existence of Andon fishermen because their permits were not managed or fulfilled by Andon fishermen, while local fishermen who agreed to consider Andon fishermen had managed or fulfilled their permits so that they had a strong legal basis to utilize the fisheries resources in Balikukup village. Where as Andon fishermen consider that they also have the right to be involved in utilizing fisheries resources, because Andon fishermen who enter the waters of Balikukup village have managed and obtained fishing licenses. The local fisherman who rejected the existence of andon fishermen was the majority group, among which consisted of influential figures in Balikukup village, who then petitioned against the existence of Andon fishermen, who considered not fulfilling the rules of government regulation No. 36/2014 concerning fishing andon, this regulation was made to regulate but have weaknesses where no regulation on the type of fishing gear and fishing aids was allowed or not allowed, so that weaknesses could be provided space for conflicts between fishermen.